1994
DOI: 10.1007/bf00365729
|View full text |Cite
|
Sign up to set email alerts
|

What do advanced cancer patients know of their disease?

Abstract: The aim of this work was to investigate the awareness of diagnosis, prognosis and meaning of palliative treatment in Italian patients with advanced, incurable cancers. A group of 100 patients, referred to a Medical Oncology facility, were interviewed. Only 38 patients were aware of the malignant neoplastic nature of their disease. The remaining patients believed they had a benign neoplasia, non-neoplastic disease, or were unable to define their illness. No patient had a correct idea of the poor prognosis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 10 publications
8
102
1
2
Order By: Relevance
“…This parallels previous studies that found similar rates of prevalence of diagnosis non-disclosure among oncological patients [8,31,32], for example in Italy and Taiwan. These results provide continued support for the disclosure of cancer diagnosis as a standard practice, especially given that it is well-documented that withholding disclosure of cancer diagnosis generates long-term imbalance and distrust in doctor-patient relationship [33,34] and future lack of communication about cancer and disease-related issues [14,35].…”
Section: Discussionsupporting
confidence: 91%
“…This parallels previous studies that found similar rates of prevalence of diagnosis non-disclosure among oncological patients [8,31,32], for example in Italy and Taiwan. These results provide continued support for the disclosure of cancer diagnosis as a standard practice, especially given that it is well-documented that withholding disclosure of cancer diagnosis generates long-term imbalance and distrust in doctor-patient relationship [33,34] and future lack of communication about cancer and disease-related issues [14,35].…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that, for all the topics covered in the questionnaire, a clear distinction can be made between opinion and behaviour, the only remarkable exception being the issue of whether or not to tell patients, which remains unresolved [4,13,17]. The uncertainty on this topic underlines the importance of a physician/patient relationship, which can be deep and is always unique [1, 6, 11, 121.…”
Section: Discussionmentioning
confidence: 98%
“…174 Correspondingly, patients fre quently report not knowing their prognosis 95,175 or overestimate their prognosis, even when provided accurate information. 95,105,[176][177][178][179][180][181][182] In these studies, higher educational level, lower levels of depression, and higher patient ratings of their physician were associated with better understanding, but further research is needed to examine causal relationships among these factors.…”
Section: Patient-centered Communication In Cancer Carementioning
confidence: 99%